The development, reliability, and validity of the facilitator assessment tool: an implementation fidelity measure used in parenting for lifelong health for young children - Martin, M; Lachman, JM; Murphy, H; Gardner, F; Foran, H (Wiley, 2022)
Background: The Parenting for Lifelong Health for Young Children (PLH-YC) programme aims to reduce violence against children and child behaviour problems among families in low- and middle-income countries (LMICs). Although the programme has been tested in four randomised controlled trials and delivered in over 25 countries, there are gaps in understanding regarding the programme's implementation fidelity and, more generally, concerning the implementation fidelity of parenting programmes in LMICs. Aims: This study aims to address these gaps by examining the psychometric properties of the PLH-YC-Facilitator Assessment Tool (FAT)—an observational tool used to measure the competent adherence of PLH-YC facilitators. Examining the psychometric properties of the FAT is important in order to determine whether there is an association between facilitator competent adherence and programme outcomes and, if correlated, to improve facilitator performance. It is also important to develop the implementation literature among parenting interventions in LMICs. Methods: The study examined the content validity, intra-rater reliability, and inter-rater reliability of the FAT. Revision of the tool was based on consultation with programme trainers, experts, and assessors. A training curriculum and assessment manual was created. Assessors were trained in Southeastern Europe and their assessments of facilitator delivery were analysed as part of a large-scale factorial experiment (N = 79 facilitators). Results: The content validity process with PLH-YC trainers, experts, and assessors resulted in substantial improvements to the tool. Analyses of percentage agreements and intraclass correlations found that, even with practical challenges, assessments were completed with adequate yet not strong intra- and inter-rater reliability. Conclusions: This study contributes to the literature on the implementation of parenting programmes in LMICs. The study found that the FAT appears to capture its intended constructs and can be used with an acceptable degree of consistency. Further research on the tool's reliability and validity—specifically, its internal consistency, construct validity, and predictive validity—is recommended.